1999
DOI: 10.1021/jp9838543
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio Studies of NH4+(H2O)1-5 and the Influence of Hydrogen-Bonding Nonadditivity on Geometries and Vibrations

Abstract: Ab initio calculations were performed to investigate the structures, energetics, and vibrations of NH4 +(H2O) n cluster ions at n = 0−5. Equilibrium geometries of NH4 + and NH4 +−H2O are optimized at the MP2, MP4, CCD, QCISD, and B3LYP levels using the 6-31G*, 6-31G**, 6-31+G*, 6-31++G**, 6-311+G**, and 6-311++G** basis sets. The benchmark calculations indicate that using MP2 and B3LYP approaches with the 6-31+G* basis set is well suited for characterizing large NH4 +(H2O) n clusters. The two approaches corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
52
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 53 publications
12
52
0
Order By: Relevance
“…4 are (1) the good agreement in entropy trends between our work and those from HPMS experiments by Meot-Ner and coworkers as well as results from a combined density functional (B3LYP) and ab initio study (MP2-level) reported by Jiang et al (1999) (Note, entropy changes have been calculated from Jiangs' reported MP2-level hydration enthalpies and free energies up to m = 5 and added (2) the excellent agreement between our calculated and reported (Meot-Ner, 1984) incremental hydration enthalpies and entropies up to the NH 4 þ ÁðH 2 OÞ 6 cluster. A key feature that emerges from recent IR-studies of NH 4 þ ÁðH 2 OÞ n clusters by Chang et al (1998) and Jiang et al (1999) is a strong temperature dependence of the ring opening and closing process in NH 4 þ ÁðH 2 OÞ 5 (f5) and NH 4 þ ÁðH 2 OÞ 6 (f6). The closure toward the ring structures f5 and f6 as shown in Fig.…”
Section: Nh 4 þsupporting
confidence: 85%
See 3 more Smart Citations
“…4 are (1) the good agreement in entropy trends between our work and those from HPMS experiments by Meot-Ner and coworkers as well as results from a combined density functional (B3LYP) and ab initio study (MP2-level) reported by Jiang et al (1999) (Note, entropy changes have been calculated from Jiangs' reported MP2-level hydration enthalpies and free energies up to m = 5 and added (2) the excellent agreement between our calculated and reported (Meot-Ner, 1984) incremental hydration enthalpies and entropies up to the NH 4 þ ÁðH 2 OÞ 6 cluster. A key feature that emerges from recent IR-studies of NH 4 þ ÁðH 2 OÞ n clusters by Chang et al (1998) and Jiang et al (1999) is a strong temperature dependence of the ring opening and closing process in NH 4 þ ÁðH 2 OÞ 5 (f5) and NH 4 þ ÁðH 2 OÞ 6 (f6). The closure toward the ring structures f5 and f6 as shown in Fig.…”
Section: Nh 4 þsupporting
confidence: 85%
“…Experimental clustering equilibria for NH 4 þ ÁðH 2 OÞ m and NH 4 þ ÁðH 2 SÞ n are taken from HPMS studies by Meot-Ner and Speller (1986), Meot-Ner (1984), Payzant et al (1973) and Meot-Ner and Sieck (1985), respectively. Our discussion also includes two recent combined IR-spectroscopic and ab initio studies of ammonium-water clusters by Wang et al (1998) and Jiang et al (1999).…”
Section: H 3 S +mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, in many natural and agricultural ecosystems, NH 4 + ion is the predominant nitrogen source and an important micronutrient in the world's water system [1]. Hence, a detailed understanding of the solvation process of ammonium ion plays an important role both in chemistry and biology and the subject of extensive experimental [2][3][4][5][6][7][8][9][10] and theoretical [11][12][13][14][15][16][17][18][19][20] studies. The faster rotational dynamics of NH 4 + in water is a central focus of these studies.…”
Section: Introductionmentioning
confidence: 99%